Design of an Adaptive Fuzzy Control System for Dual Star Induction Motor Drives, ISSN / e-ISSN 1582-7445 / 1844-7600 - Youb Lamia; Sebti Belkacem; Naceri Farid; Mihai CERNAT; Guasch-Pesquer Luis (Advances in Electrical and Computer Engineering, 2018)
In this paper, a new control stra¬tegy is deve¬loped; an adaptive fuzzy controller based on Lyapunov's stability theory (AFLC) recalculates the real-time PI-fuzzy gains and combines the advantages of two robust techniques i.e. the fuzzy logic control and the adaptive one. For the new adaptive fuzzy control, we followed two steps: in the first one, a PI-fuzzy controller is designed, in the second step, the gains of a fuzzy regulator are determined. Extensive simulation results are presented to validate the proposed technique. The system is tested at different speeds and a very satisfactory performance has been achieved.